Factors influencing the difficulty of laparoscopic myomectomy: the development of a surgical rating tool. (December 2018) - Leung, Marian; Murji, Ally; Allaire, Catherine; Singh, Sukhbir S.; Thiel, John; Tulandi, Togas; Shore, Eliane M.
Abstract: Objective To obtain expert consensus on the patient and fibroid characteristics that affect the complexity of laparoscopic myomectomy (LM) and to use these factors to create a grading tool for objective evaluation of LM procedures. Study design Modified Delphi Methodology Study (Canadian Task Force III). Setting included a series of online surveys via SurveyMonkey (SurveyMonkey Inc., San Mateo, California, USA). Participants were Canadian minimally invasive gynecologic surgeons (MIGS) who perform LM. A list consisting of patient, uterine and procedural characteristics was disseminated to Canadian MIGS. Opportunity to include additional factors was provided. Consensus was predefined as Cronbach's α of ≥0.80. A second Delphi survey was then done to assign weight value for each item in the grading tool. Results Twenty-seven surgeons from across Canada participated. Most (23/27, 85%) were MIGS fellowship trained, and performed more than 6 LM per year (18/27, 66.7%). Consensus was achieved in the first round of the survey (Cronbach's α = 0.93). Sixteen of 27 factors met the criteria for inclusion (>80% respondents agreed or strongly agreed) and were included in the final rating tool. Factors that met the criteria for inclusion were grouped as patient factors (including body mass index), uterine factors (including number of fibroids, size of largest fibroid), and surgical factors (including ease of developing the cleavage plane). Conclusions Using the Delphi methodology to obtain expert consensus on the factors influencing the difficulty of LM, we have developed an objective grading tool to evaluate the degree of technical complexity of LM.